2016
DOI: 10.1590/1678-775720150399
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser and/or fluoride enamel treatment against in situ/ex vivo erosive challenge

Abstract: Objective This in situ/ex vivo study investigated the effect of CO2 laser irradiation and acidulated phosphate fluoride gel (APF) application, separately and in combination, on enamel resistance to erosion.Material and Methods During 2 experimental 5-day crossover phases, 8 volunteers wore intraoral appliances containing bovine enamel blocks which were submitted to four groups: 1st phase - control, untreated and CO2 laser irradiation, 2nd phase - fluoride application and fluoride application before CO2 laser i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In our study, enamel micro-hardness of the permanent teeth in the fluoride group significantly decreased after the erosive process. Jordao et al, 24 Sobral et al, 21 and Scatolin et al 33 showed that APF gel decreased the erosive loss of bovine enamel. This controversy in the results may be due to the difference in the study design in terms of the type of tooth, pH cycling and the quantitative method of erosion assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, enamel micro-hardness of the permanent teeth in the fluoride group significantly decreased after the erosive process. Jordao et al, 24 Sobral et al, 21 and Scatolin et al 33 showed that APF gel decreased the erosive loss of bovine enamel. This controversy in the results may be due to the difference in the study design in terms of the type of tooth, pH cycling and the quantitative method of erosion assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have assessed the efficacy of fluoride alone and in combination with other protective measures in the prevention of erosion. 3,24,[39][40][41][42] Laser irradiation alone or combined with fluoride application has also been suggested to increase enamel acid resistance, 31,43 and some studies demonstrated the positive efficacy of Er:YAG laser in increasing enamel resistance against acid attacks and dental caries. 30,31,44 Although both caries and erosion are caused by the demineralization of enamel, their main etiologic factors and mechanism of development are totally different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Er:YAG lasers (2.94 µm) have been studied regarding the prevention of enamel demineralization and produced positive results when enamel was subjected to cariogenic challenges 4 , 5 . However, few data have shown whether irradiated enamel would react in the same manner when subjected to erosion 12 , 18 , 22 and erosion associated with abrasion challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth structure loss due to erosive and abrasive challenges is irreversible, and several strategies have been developed with the aim of preventing damage, including the use of high-intensity lasers 12 . To increase the acid resistance of the enamel, the use of an Er:YAG laser has been proposed 4 , 7 .…”
Section: Introductionmentioning
confidence: 99%